1976
DOI: 10.1021/jm00225a012
|View full text |Cite
|
Sign up to set email alerts
|

New series of cardioselective adrenergic .beta.-receptor blocking compounds. 1-(2-Acyl-4-acylaminophenoxy)-3-isopropylaminopropan-2-ols

Abstract: A series of 1-(2-acyl-4-acylaminophenoxy)-3-isopropylaminopropan-2-ols has been synthesized and examined for beta-receptor blocking and antiarrhythmic activity. Several of these compounds are more than 20 times as active in blocking cardiac beta-receptors than vascular beta-receptors when given intravenously to anesthetized cats. The activities have been correlated quantitatively with partition and steric substitution constants. The observed relationships are consistent with a tentative proposal that the vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Comparison of the 3rd and 4th columns of Table 1 shows that acebutolol and M&B 19421 were more active antagonists at /31-than #2-adrenoceptors and that M&B 16942A was equally effective on both types of receptor. This confirms the findings of Basil et al (1976). The present results also agree with those of Maxwell & Collins (1974); in both studies acebutolol was more selective for the cardiac #l,-receptors than the bronchial 32-receptors.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Comparison of the 3rd and 4th columns of Table 1 shows that acebutolol and M&B 19421 were more active antagonists at /31-than #2-adrenoceptors and that M&B 16942A was equally effective on both types of receptor. This confirms the findings of Basil et al (1976). The present results also agree with those of Maxwell & Collins (1974); in both studies acebutolol was more selective for the cardiac #l,-receptors than the bronchial 32-receptors.…”
supporting
confidence: 93%
“…The following drugs were used: isoprenaline sulphate (Burroughs Wellcome); (±+propranolol (ICI); acebutolol and two of its analogues, M&B 16942A and 19421 (May and Baker). Details of the analogues of acebutolol are given in Table 1 of the paper by Basil, Clark, Coffee, Jordan, Loveless, Pain & Wooldridge (1976). The compounds chosen for the present experiments were Compound 1, M&B 16942A…”
mentioning
confidence: 99%
“…The usual synthesis of racemic 3-aryloxy-1-isopropylamino-2-propanol proceeds via the aminolysis of respective glycidylaryl ethers with isopropylamine [12,13]. Atenolol (1), a widely known antihypertensive drug, was usually prepared [14] by the standard procedure given in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…Acebutolol is used in the treatment of high blood pressure, abnormal heart rhythms, and sometimes chest pain . Similar to other β ‐blockers, acebutolol is used as a racemic mixture, despite the fact that its β ‐blocking activity is attributed to the S ‐enantiomer and its major metabolite S ‐diacetolol .…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Acebutolol is used in the treatment of high blood pressure, abnormal heart rhythms, and sometimes chest pain. [11][12][13][14][15][16][17] Similar to other β-blockers, acebutolol is used as a racemic mixture, despite the fact that its β-blocking activity is attributed to the S-enantiomer and its major metabolite S-diacetolol. 18 Moreover, it has been reported that both the enantiomers of adrenergic β-receptor blockers are not only different from the pharmacodynamic point of view but their pharmacokinetic properties are also very different.…”
mentioning
confidence: 99%